(Re) discovering the business purpose: A discursive approach to CSR and stakeholder management. Issue 4 (3rd December 2019) - Atif, Muhammad
Abstract : Purpose: This study aims to focus on the purpose and legitimacy of business, notably, the organizational purpose, the conventional view that the purpose of business is to optimize the returns to shareholders, and the emerging view that organizations serve multiple purposes including economic returns. Design/methodology/approach: This study applies Habermas's discourse ethics to corporate social responsibility (CSR) and stakeholder management (SHM) and argues that discourse ethics is a balanced philosophical approach, which can effectively address the limitations of CSR and SHM. Findings: The analysis demonstrates that discourse ethics is a distinctive philosophical approach to ethical theory and has high relevance to the field of CSR and SHM. Originality/value: The discursive approach to CSR and SHM is unique because it allows assimilating various ethical situations – from pragmatic to normative – under one theoretical framework. The potential of the proposed approach is illustrated through a thorough discussion of its application to CSR and SHM.